Spectroscopic characterization, X-ray structure and DFT studies on 4-[3-(2,5-dimethylphenyl)-3-methylcyclobutyl]-N-methylthiazol-2-amine - Saracoglu, H.; Ekici, O. (Pleiades Publishing Inc, 2015)
The titled molecule 4-[3-(2,5-dimethylphenyl)-3-methylcyclobutyl]-N-methylthiazol-2-amine (C17H22N2S) is synthesized and characterized by H-1 NMR, C-13 NMR, IR, and X-ray single crystal determination. The compound crystallizes in the monoclinic space group P2(1/c) with a = 6.3972(4) , b = 9.4988(6) , c = 26.016(2) and beta = 93.496(7)A degrees. In addition to the molecular geometry from the X-ray determination, vibrational frequencies and gauge, including the atomic orbital (GIAO), H-1 and C-13 NMR chemical shift values of the titled compound in the ground state are calculated using the density functional (B3LYP) method with 6-31G(d), 6-31++G(d,p) and 6-311+G(2d,p) basis sets. The calculated results show that the optimized geometries can well reproduce the crystal structure. Moreover, the theoretical vibrational frequencies and chemical shift values show good agreement with the experimental values. The predicted nonlinear optical properties of the titled compound are greater than those of urea. DFT calculations of the molecular electrostatic potentials and frontier molecular orbitals of the titled compound are carried out at the B3LYP/6-31G(d) level of theory.
Keywords: synthesis; thiazole; computational chemistry; X-ray structure determination; NMR spectroscopy; nonlinear optical properties